(untitled) (Libellarium: journal for research in the field of information and related sciences, 2024)
Purpose. The paper analyzes the inclusive UI/UX design in the virtual environment for elderly people, those above 65 years old. Approach/methodology/design. The research was conducted from August 1 to 13, 2023, using an online questionnaire shared with a group of elderly people on social media. Findings. The research has shown that elderly people use mobile devices extensively to browse content on social media, read and follow news portals, and communicate. The respondents have exhibited a good level of self-confidence when interacting with user interfaces. However, they cited several issues with digital services and products, such as insufficiently highlighted elements on the user interface, inability to adjust typography elements, poor colour contrast, etc. The aids and assistive technologies the respondents use when interacting in a virtual environment are voice commands and a screen magnifier. The respondents indicated needing help when using social media (Facebook), visiting a website for the first time, sending a message, navigating websites, installing new applications, turning on GPS, or Internet banking. Research limitations/implications. The respondents, participants in the research, are mostly from Osijek-Baranja County, so they are not a representative sample of the elderly people in the Republic of Croatia. Practical implications. Theoretical knowledge and the results of the conducted research contribute to a better understanding of the components of inclusive design of user interfaces, especially for specific groups of users. Social implications. This paper contributes to increasing awareness of the importance of adapting digital products and services to users, especially the elderly. Originality/value. The study presents the results of one of the rare pieces of research on inclusive design among elderly people. The paper raises awareness of the much-needed inclusion of elderly people in the virtual environment.